1986
DOI: 10.1111/j.1464-5491.1986.tb00808.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐induced Hypoglycaemia and Subcutaneous Insulin Infusion

Abstract: To assess whether exercise-induced hypoglycaemia could be prevented by interruption of insulin infusion (3 h) we studied diabetic patients treated with continuous subcutaneous insulin infusion (CSII). The studies were performed in 7 insulin-dependent diabetics (aged 31.4 +/- 4.8 (mean +/- SD) years, duration of diabetes 16.9 +/- 5.4 years), after an overnight fast and in the afternoon, 4 h after the last pre-meal bolus injection (exercise and control period). Bicycle exercise (45 min at 60% of maximum oxygen c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Conversely, Admon et al 12 found similar rates of hypoglycemia during 45 min of moderate aerobic activity performed 2 h after breakfast whether basal insulin was suspended or not. Where afternoon exercise was performed (as was the case in our study), Edelmann et al 11 found that if basal insulin was suspended for 3 h (starting 30 min prior to exercise), it was insufficient to prevent hypoglycemia during exercise. In contrast, Tsalikian et al 8 found that suspending basal insulin at the start of exercise limited the frequency of hypoglycemia during the activity (16% vs. 43% in pump off vs. pump on trials) but resulted in more post-exercise hyperglycemia (27% vs. 4%).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Conversely, Admon et al 12 found similar rates of hypoglycemia during 45 min of moderate aerobic activity performed 2 h after breakfast whether basal insulin was suspended or not. Where afternoon exercise was performed (as was the case in our study), Edelmann et al 11 found that if basal insulin was suspended for 3 h (starting 30 min prior to exercise), it was insufficient to prevent hypoglycemia during exercise. In contrast, Tsalikian et al 8 found that suspending basal insulin at the start of exercise limited the frequency of hypoglycemia during the activity (16% vs. 43% in pump off vs. pump on trials) but resulted in more post-exercise hyperglycemia (27% vs. 4%).…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, too aggressive a reduction in basal and/or bolus insulin, as may occur with pump suspension, may contribute to exercise-associated hyperglycemia, particularly in the postexercise period. [7][8][9] A limited number of studies have examined the glycemic response to exercise in patients with type 1 diabetes receiving insulin by constant infusion, 8,[10][11][12] although few have actually compared CSII versus MDI. Sonnenberg et al 10 found that, when performing 60 min of moderate aerobic exercise in the morning 90 min after breakfast, hypoglycemia occurred in more than half of their CSII participants unless the pre-meal bolus was decreased by 50% and the basal insulin infusion was suspended during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…A more detailed analysis of the afternoon post‐exercise shows that the best option for exercise at 50% VO 2 max 3 h after lunch is 80% BR reduction throughout exercise and the ensuing 2 h. This approach offers an intermediate solution between reducing BR by 50% before exercise, as recommended by some authors and stopping the pump, which has also been proposed . For exercise at 75% VO 2 max, the best option is to stop the pump temporarily during exercise, which reflects fairly well the wish of certain patients to remove their pump.…”
Section: Discussionmentioning
confidence: 92%
“…reducing BR by 50% before exercise, as recommended by some authors [4,10,[17][18][19][20] and stopping the pump, which has also been proposed [21,22]. For exercise at 75% VO 2 max, the best option is to stop the pump temporarily during exercise, which reflects fairly well the wish of certain patients to remove their pump.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on continuous subcutaneous insulin infusion have shown that reducing the action of the pump by 50% before exercise, similar to multiple component regimens, prevents hypoglycaemia. [29][30][31] LISPRO Lispro is a rapid acting insulin analogue which has recently been developed, particularly for injection immediately before a meal. Its rapid absorption and short duration of action provide several advantages, and, although reports on Lispro and exercise are limited, the use of a shorter acting analogue will probably allow a greater degree of flexibility and the ability to accommodate short term planning or unexpected exercise.…”
Section: Insulin Pumpsmentioning
confidence: 99%